2013
DOI: 10.2460/javma.243.9.1323
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic removal of a bladder urolith in a standing horse

Abstract: Findings suggested that minimally invasive transparalumbar fossa laparoscopic approach can be successfully used for cystotomy and urolith extraction in standing horses; this avoids the disadvantages of conventional laparocystotomy for removal of large uroliths in male equids and the potential complications of general anesthesia and recovery. The technique provided excellent viewing and access to the bladder, permitting extraction of the urolith and secure closure of the cystotomy with minimal tension and tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…All bladders were from normal horses and had varying degrees of autolysis prior to performance of each procedure. Thus, any sample handling and tissue preservation would have weakened the bladder wall, which would make them more comparable to clinical cystorrhexis, where tissue trauma, inflammation, and necrosis are often present . Furthermore, all of the bladders in the present study were from adult horses.…”
Section: Discussionmentioning
confidence: 97%
“…All bladders were from normal horses and had varying degrees of autolysis prior to performance of each procedure. Thus, any sample handling and tissue preservation would have weakened the bladder wall, which would make them more comparable to clinical cystorrhexis, where tissue trauma, inflammation, and necrosis are often present . Furthermore, all of the bladders in the present study were from adult horses.…”
Section: Discussionmentioning
confidence: 97%
“…Although this study found no advantage to the use of use of barbed suture, this approach may be more advantageous to reduce the duration of laparoscopic procedures. Laparoscopic closure of a cystotomy has been described after urolith removal, mass excision, and placement of a percutaneous urinary catheter in large animals . The technical challenge associated with intracoporeal knot tying is compounded by a confined working space with limited visualization, increasing the duration of laparoscopic procedures .…”
Section: Discussionmentioning
confidence: 99%
“…On the standing horse, pararectal and perineal urethrotomy have been described (Laverty et al 1992;Beard 2004;Foley et al 2009;Schott and Woodie 2012;Hawkins 2013). Recently, efforts have been made to reduce the invasiveness of the procedure by introducing laparoscopic or laparoscopic-assisted techniques, either standing or under general anaesthesia, and transendoscopic lithotripsy techniques on standing sedated horses (Ragle 2002;Röcken et al 2006Röcken et al , 2012Lund et al 2013;Vitte et al 2013). Even if the latter techniques, particularly electrohydraulic lithotripsy, have become the first treatment option for certain surgeons (Röcken 2013), they require expensive equipment, are time consuming, do not allow fragmentation of all calculi and still carry risks of complications (Röcken et al 2012;Hawkins 2013;Reichelt and Lischer 2013).…”
Section: Discussionmentioning
confidence: 99%